Determinants for Acceptability of a Conditional Cash Transfer Scheme (Janani Suraksha Yojana) for Encouraging Institutional Deliveries among Antenatal Mothers: A Case Control Study. (June 2018) - Kumar, Avinash; Unnikrishnan, B.; Rekha, T.; Mithra, Prasanna; Kumar, Nithin; Kulkarni, Vaman; Holla, Ramesh; Darshan, B.B.; Chekragari, Manognya
The objective of this artile is to assess the determinants of acceptance of conditional cash transfer scheme (Janani Suraksha Yojana [JSY]) among antenatal women in Mangalore.The study is on matched case control study. The study has been carried out in the Government maternity hospital of Manipal University and on the antenatal women visiting government hospital for Ante natal care (ANC) and belonged to below poverty line. Total of 136 pregnant females, that is, 68 cases (availing conditional cash benefit) and 68 controls (not availing conditional cash benefit), were recruited in the study. A pretested semi-structured questionnaire was used as data collection tool. The association between the educational status of the participant and their acceptance of JSY and association between the educational status of the participant's spouse and acceptance of JSY by their wives has been found to be statistically significant. The JSY has been successfully promoting institutional deliveries.